Detecting sensitive areas in confined shallow basins. (April 2020) - De Serio, Francesca; Armenio, Elvira; Ben Meftah, Mouldi; Capasso, Gennaro; Corbelli, Vera; De Padova, Diana; De Pascalis, Francesca; Di Bernardino, Annalisa; Leuzzi, Giovanni; Monti, Paolo; Pini, Agnese; Velardo, Raffaele; et al.
Abstract: Coastal shallow basins are often heavily anthropized and greatly exposed to environmental risk areas, thus requiring strict monitoring action by local authorities and stakeholders. Preventive measures against environmental degradation and early warning to hazards have been proved to benefit from the combined use of numerical models and field measurements. The present work sets out to show the potential of a meteorological-hydrodynamic model system, validated with field data, to identify the main physical processes characterizing a semi-enclosed basin located in the inner part of the Ionian Sea, in southern Italy. Furthermore, based on the model results, we adopted some convenient indicators, especially related to flow exchanges, in order to identify and characterize the area in the basin most sensitive to environmental problems. The results highlight the retentive feature of the inner part of the basin and different times necessary for the water renewal in both the surface and bottom layers. Highlights: Meteorological and hydrodynamic models to investigate physical processes in a coastal basin. Field measurements calibrating numerical models. Indicators selected to identify sensitive areas in the basin.